If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.25(4-8x)=7-(3x+5)
We move all terms to the left:
0.25(4-8x)-(7-(3x+5))=0
We add all the numbers together, and all the variables
0.25(-8x+4)-(7-(3x+5))=0
We multiply parentheses
-2x-(7-(3x+5))+1=0
We calculate terms in parentheses: -(7-(3x+5)), so:We get rid of parentheses
7-(3x+5)
determiningTheFunctionDomain -(3x+5)+7
We get rid of parentheses
-3x-5+7
We add all the numbers together, and all the variables
-3x+2
Back to the equation:
-(-3x+2)
-2x+3x-2+1=0
We add all the numbers together, and all the variables
x-1=0
We move all terms containing x to the left, all other terms to the right
x=1
| 4x^2+12x=144 | | 2/5m=260 | | -4x-26=6 | | 4x+55=137 | | x+x+(2x+10)+(2x+10)=50 | | 82-x+3=(2+4x) | | c4−2=2 | | (5+3x)x12=72 | | -3a-30+10a=5 | | x.0.25(4-8x)=7-(3x+5) | | 1.6(s-2)=8 | | 20/x=30 | | 3y+5=100 | | -3/r=3 | | ∠B=x93∘ | | x=74=23 | | 2n=-2-3(-4) | | 8.3x-1.4=15.2 | | 13(3j+6)= | | 2(x-16)=8(x-1) | | 2x-2+3x=73 | | 2x+6=-3x+9 | | x+135=120 | | 23x-12=180 | | 1=f4−2 | | 9w–7=-7 | | 54+x=60 | | 6x+48=6(x+ | | (12+5)×16÷2+48=x | | 9=2q−5 | | 7+1(b+-4)=(7+b)+-4 | | x=3.1/3x2+2 |